Intézményi menedzsment : az egyetemi vezetés sajátosságai - Berde, Csaba; Móré, Mariann (Közép-Európai Közlemények, 2015)
This paper aim to expound the international literature,the Hungarian law came into effect after the democratic revolution and the management structures for higher education system. This article also seeks to find ways through managerial tasks are changed and assignments are delegated and shared. The authors analyze the professional structures at universities and feature the indicators and indexes of proficiency. In the authors’ opinion universities are professional organizations which mean their autonomy cannot regulate by the law. The restriction of professional independence may cause operational problems. Finally authors try to find new aspects and perspectives the definition of institutional management.